High Altitude Pulmonary Edema. Case Report and Bibliography Review - Edgar Ernesto Romo Pinos; Yojan Guevara Pérez; Rina María Idrovo Avecillas; Vilma Silvana Vele Quito (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
High altitude pulmonary edema occurs in patients who were for some days in cities at the sea level and go back to altitudes over 2,500 mosl. This edema is secundary to a pulmonary maladjustment which leads to a significant hypoxia. It is presented a case of a 15 year old girl who after being in the Ecuadorian coast returned to the mountains at Guamote canton. The objective of this report is to know the pathophisiology, diagnostic and therapeutic approach of high altitute pulmonary edema since it is a frequent condition in children of the region and it is unknown by many health professionals. Most of the times it is under diagnosed or confused with other pathologies which present with respiratory failure.